Midwifery Students' Perceptions of Utilizing Artificial Intelligence (AI) for English Language Learning (ELL) - Ningsih, Sri; Syufi, Yafed; Lakehu, Amalia (Universitas Lancang Kuning, 2025)
This study aims to explore the language politeness of elementary school students in daily interactions, analyze the integration of digital literacy in Indonesian language learning, and describe the barriers in the process. Using a qualitative approach with a phenomenological design, the research was conducted at ICT Al Abidin Elementary School in Surakarta. Data was collected through observation, interview, and documentation study, the research was analyzed using Miles and Huberman's interactive technique. The results showed that students have a fairly good level of language politeness in formal contexts, but still face challenges in informal and digital interactions. The integration of digital literacy in Indonesian language learning has been comprehensively implemented, including the use of e-books, online information search, and multimedia projects. Students show a positive response to this integration. The main barriers include access to inappropriate content and challenges in teaching language politeness in digital environments. The study concludes that despite significant progress, continued efforts are needed to maximize the potential of technology in effective and relevant Indonesian language learning in the digital era.